The Effect of Regulatory Compliance and Digital Audit Adoption on Auditor Performance and Financial Reporting Accuracy in Indonesia - Loso Judijanto; Tanti Widia Nurdiani; Tri Widyastuti Ningsih; Masdar Ryketeng (The Es Accounting And Finance, 2023)
The financial reporting landscape in Indonesia is marked by a complex interplay of regulatory compliance and the adoption of digital audit technologies. This study conducted a quantitative analysis to investigate the relationships between regulatory compliance, digital audit adoption, auditor performance, and financial reporting accuracy. The results revealed a robust positive association between regulatory compliance and both auditor performance and financial reporting accuracy. Regulatory compliance emerged as a vital driver of effective auditing and higher financial reporting accuracy in the Indonesian context. In contrast, digital audit adoption, while promising, did not exhibit a significant impact on auditor performance or financial reporting accuracy. The findings underline the importance of regulatory adherence in fostering financial transparency and accountability, and they offer valuable insights for auditors, organizations, and regulatory bodies in Indonesia.